Emerging role of SENP1 in tumorigenesis and cancer therapy - Lin, Min; Zhang, Man; Yi, Bei; Chen, Jinchi; Wen, Siqi; Chen, Ruiqi; Chen, Tianyu; Li, Zhao (Frontiers in Pharmacology, 2024)
Small ubiquitin-like modifier (SUMO)/sentrin-specific protease 1 (SENP1), a cysteine protease, plays an important role in SUMO family members maturation and target proteins deSUMOylation. Aberrant expression and regulation of SENP1 have been found in various cancers. Furthermore, the dysregulation of SENP1 is significantly related to cancer biological behaviors. This review focuses on the role of SENP1 in cancer proliferation, apoptosis, invasion, metastasis, stemness, angiogenesis, metabolism and drug resistance. Moreover, the development of SENP1 inhibitors for cancer treatment is introduced. This study aims to provide a new insight for cancer diagnosis, treatment and prognosis.